Antenatal and Postnatal Factors Associated with Offspring Adiposity During the First Two Years of Life (FS18-08-19). (13th June 2019) - Lipsmeyer, Melissa; Diaz, Eva; Sims, Clark; Cleves, Mario; Shankar, Kartik; Andres, A
Abstract: Objectives: Maternal obesity is a risk factor for the development of obesity in offspring. Yet, it is unclear what other antenatal and postnatal characteristics can also influence offspring's obesity risk. The objective of this study was to determine which factors are the strongest predictors of offspring adiposity during the first 2 years of life to better inform future intervention strategies. Methods: Two hundred and twenty-four (224) mother (BMI 18.5–35 kg/m 2 ) and child pairs (male: N = 128, female: N = 96) were included in this analysis. Percent fat mass (%FM) was obtained using quantitative nuclear magnetic resonance in children at 11 time points between age 0.5 to 24 months. Maternal race, age, gestational weight gain, first trimester %FM, delivery mode as well as averaged gestational measures of resting energy expenditure, respiratory exchange ratio, physical activity (PA), FM (BodPod®), serum cytokines, serum lipids, and dietary intake were considered as the maternal independent variables. Child's sex, birth weight and length, length of breastfeeding, and PA at 2 years of age were considered as the child's independent variables. Linear mixed models were used to construct the best-fitted models for the entire cohort and for each sex. Results: Maternal %FM, serum low density lipoprotein (LDL), high density lipoprotein (HDL), child's sex, birth weight and length of breastfeeding were independent predictors of offspring %FM in the entire cohort. When stratified by child sex, maternal %FM was the strongest predictor of girls adiposity (β = 0.14, P = 0.002) followed by maternal serum HDL levels (β = 0.07, P < 0.001). For male offspring, birth weight (β = 1.80, P = 0.01) was the strongest predictor of adiposity during the first 2 years of life followed by maternal serum HDL (β = 0.04, P = 0.013) and length of breastfeeding (β = 0.004, P = 0.005). Conclusions: Maternal obesity has a sexually dimorphic effect on offspring %FM from birth to age 2 years. In both boys and girls, maternal serum HDL levels in early pregnancy were a significant predictor of offspring FM accrual during the first 2 years of life. Further investigations on the precise mechanisms of how maternal %FM and lipid profiles can influence female compared to male offspring fat accretion are needed. Funding Sources: USDA-ARS # Project #6026-51000-010-05S.